Physical, Chemical, and Sensory Characteristics Evaluation of Bread from Composite Flour of Wheat, Cassava, Soybean, and Potato Starch with the addition of Xanthan Gum - Pitaria Ferawati S.; Ismed Suhaidi; Zulkifli Lubis (Universitas Sumatera Utara, 2014)
The aim of this research was to find physical, chemical, and sensory characteristics evaluation of bread from composite flour of wheat, cassava, soybean, and potato starch with the addition of xanthan gum. This study was conducted to determine the physical, chemical, and sensory characteristic of bread from composite flour (wheat, cassava, soybean, and potato starch) with the addition of xanthan gum. The research was conducted in July-August 2013 in the Laboratory of Food Technology, Faculty of Agriculture, USU, Medan, used a completely randomized design with two factors : the proportion of flour in composite flour(T) ; (100 : 0 : 0 : 0 ; 50 : 15 : 15 : 20 ; 50 : 25 : 10 : 15 ; 50 : 35 : 5 : 10, and 50 : 45 : 0 : 5) and xanthan gum concentrations (G) ; (0 % , 0,5 %, and 1 %). The parameters analyzed were moisture content, ash content, fat content, fiber content, protein content, bread volume, organoleptic value of color, aroma, flavor, and texture. The results showed that the ratio of wheat, cassava, soybean, and potato starch had highly significant effect on water content, ash content, fat content, fiber content, protein content, bread volume, and value of organoleptic color, aroma, flavor, and texture. Concentration of xanthan gum gave highly significant effect of the fiber content, bread volume, value of organoleptic color, flavor, texture but had no significant on moisture content, ash content, fat content, protein content, and aroma. Interaction of these two factors had highly significant effect on water content, fat content, protein content, bread volume, and value of organoleptic texture. Proportion of wheat flour, cassava, soybean, and potato starch of (50 : 15: 15 : 20) and 1 % xanthan gum produced bread with the best quality. Keywords : bread, cassava, composites flour, soybean, xanthan gum